PSORIATIC ARTHRITIS MUTILANS IN A BLACK NIGERIAN PATIENT: A CASE REPORT - Yerima A (Ntec Specialist, 2018)
Background: Psoriatic Arthritis Mutilans (PAM) is a rare destructive form of arthritis, especially in blacks and its diagnosis and treatment still remains a challenge. Case Report: A 55-year-old house wife with 30-year history of psoriatic skin lesions, developed swellings and pain of the small joints of the hands and feet, wrists, elbows, shoulders and knees associated with low back pain and alternating buttock pain shortly after onset of the rashes. She had dystrophic, pitting, yellowish nail changes with sub-ungual hyperkeratosis. The joint swellings rapidly progressed into shortening of the digits of her hands and feet, with resorption of the interphalangeal joints and subluxation of the metarcarpophalangeal joints (MCPJs). Her Body Mass Index at presentation was 19.8kg/m, she had subluxation of the MCPJs with shortening and telescoping of the 3rd, 4th and 5th digits of both hands and bilateral knee swelling with ankylosis. Her rheumatoid factor was negative, CRP was 36mg/dl, white cell count of 3.0×109 cells/L with predominant lymphocytosis (63%). Her serum urea, creatinine and uric acid were normal. Radiographs of the hands and feet showed 'pencil in cup' appearance with marked periosteal reaction and osteolysis, complete joint erosion and subluxation. A diagnosis of PAM was made using ClASsification for Psoriatic ARthritis (CASPAR) criteria. She was placed on methotrexate 10mg weekly and topical steroids with short course of naproxen and was advised for total knee replacement and biologic agents for her treatment. Conclusion: PAM still remains a challenge in terms of early detection of the characteristic phenotype and treatment